Posterior and Anterior Spinal Fusion for the Management of Deformities in Patients with Parkinson's Disease. (2nd September 2013) - Sato, Masashi; Sainoh, Takeshi; Orita, Sumihisa; Yamauchi, Kazuyo; Aoki, Yasuchika; Ishikawa, Tetsuhiro; Miyagi, Masayuki; Kamoda, Hiroto; Suzuki, Miyako; Kubota, Gou; Sakuma, Yoshihiro; Inage, Kazuhide; et al.
Abstract : Introduction . Spinal scoliosis and kyphosis in elderly people sometimes cause severe low back pain. Surgical methods such as osteotomy are useful for correcting the deformity. However, complications during and after surgery are associated with the osteotomy procedure. In particular, it is difficult to manage deformity correction surgery for patients with Parkinson's disease. Here, we present two cases of combined anterior and posterior surgery for deformity in patients with adult scoliosis and kyphosis due to Parkinson's disease. Case Presentation . Two 70-year-old women had spinal scoliosis and kyphosis due to Parkinson's disease. They had severe low back pain, and conservative treatment was not effective for the pain. Surgery was planned to correct the deformity in both patients. We performed combined posterior and anterior correction surgery. At first, posterior fusions were performed from T4 to the ilium using pedicle screws. Next, cages and autograft from the iliac crest were used in anterior lumbar surgery. The patients became symptom free after surgery. Bony fusion was observed 12 months after surgery. Conclusions . Combined posterior and anterior fusion surgery is effective for patients who show scoliosis and kyphosis deformity, and symptomatic low back pain due to Parkinson's disease.